Integrative and Activity-Based Approach to Modeling the Professional Personality of an International Relations Student - Samorodova, Ekaterina; Merzouk, Samira (Journal of Education Culture and Society, 2025)
Aim. The main goal is to reveal the essence of the professional personality of an international relations student, as well as to confirm the integrative and activity-based approach as a methodological basis for practical activities and their formation, to determine the main characteristics of this approach, which together provide a new quality of education.Methods. Based on comparative and systemic methods of analysis, the activity-based approach is characterized as part of the integrative and activity-based approach. An analysis of a business/role play as an implementation of the integrative and activity-based approach in the formation of a professional international relations student is conducted in paper.Results. In the course of reasoning are revealed the essence of the professional personality, its main features as interculturality/cross-culturality, polyvalence, human-centeredness and integrativity of an international relations student and the role of the university learning environment in the process of its development; , is demonstrated an example of modeling the professional personality of international relations students in the process of obtaining higher education based on the integrative and activity-based approach during a business/role play, as one of the types of its implementation.Conclusions. The integrated activity approach is key in the formation of the professional personality of an international relations student. A business/role play as one of the forms of implementing the integrated activity approach fully forms the necessary aspects of the professional personality of a student in the course of solving educational problems.